2018
DOI: 10.1002/ajhb.23107
|View full text |Cite
|
Sign up to set email alerts
|

Dental enamel defects predict adolescent health indicators: A cohort study among the Tsimane’ of Bolivia

Abstract: Defective enamel formation in infancy and childhood predicted adolescent health outcomes and may be primarily associated with infection. Extent of enamel defects and stunted growth may be equally predictive of adverse adolescent health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
2
0
3
Order By: Relevance
“…Recent research on modern adolescents (10‐17 years) from the Bolivian Amazon found an association between developmental enamel defects and parasitic infections (hookworm; Masterson et al, 2017), but no association between childhood parasitic infection and adolescent health outcomes. However, a relationship was established between enamel defects and anemia (Masterson et al, 2018), and in modern populations, a high prevalence of anemia is related to a high infectious disease load (Engle‐Stone et al, 2017). Parasitic infection and anemia were endemic in the Colorado Plateau (Kent, 1986; Reinhard, 1992; Reinhard & Clary, 1986; Stodder & Martin, 1992), and chronic infection is thought to be the primary cause of anemia at Hawikku (Stodder & Martin, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on modern adolescents (10‐17 years) from the Bolivian Amazon found an association between developmental enamel defects and parasitic infections (hookworm; Masterson et al, 2017), but no association between childhood parasitic infection and adolescent health outcomes. However, a relationship was established between enamel defects and anemia (Masterson et al, 2018), and in modern populations, a high prevalence of anemia is related to a high infectious disease load (Engle‐Stone et al, 2017). Parasitic infection and anemia were endemic in the Colorado Plateau (Kent, 1986; Reinhard, 1992; Reinhard & Clary, 1986; Stodder & Martin, 1992), and chronic infection is thought to be the primary cause of anemia at Hawikku (Stodder & Martin, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…LEH acts as an indicator of adaptive plasticity and physiological constraint, because it reflects an interim period when energetic resources are diverted from enamel production to maintain vital developmental processes that have short‐term survival benefits but potential long‐term consequences (Temple, 2019). In living populations, LEH is prevalent in underdeveloped countries, famine populations, and rural communities (Chaves, Rosenblatt, & Oliveira, 2007; Goodman & Rose, 1991; Kanchanakamoll et al, 1996; Nikiforuk & Fraser, 1981; Oliveira, Chaves, & Rosenblatt, 2006; Rugg‐Gunn, Al‐Mohammadi, & Butler, 1998; Sweeney, Cabrera, Urrutia, & Mata, 1969; Zhou & Corruccini, 1998), and enamel defects in infancy are associated with malnutrition and adverse health outcomes in adolescence (Goodman & Rose, 1991; Masterson et al, 2017; Masterson et al, 2018). Generally, increases in LEH prevalence in the past correlate with major dietary, settlement, and behavioral shifts (eg, the agricultural transition, European colonization) (Cook, 1984; Goodman, Armelagos, & Rose, 1984; Larsen, 1994; Larsen et al, 2001; Littleton, 2005; Santos & Coimbra Jr., 1999; Ubelaker, 1984; Wright, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Por lo tanto, los trastornos en la función de los ameloblastos y/o de los odontoblastos durante el desarrollo del diente dan lugar a defectos permanentes, ya que una vez formado el esmalte dental es un tejido acelular que no tiene capacidad reparadora, salvo el efecto protector y remineralizador de la saliva en la etapa posteruptiva. Los DDE se consideran desviaciones de la apariencia y estructura normal del esmalte dental resultantes de una disfunción en el órgano del esmalte 35,37,38 .…”
Section: Defectos De Esmalteunclassified
“…En Latinoamérica se han desarrollado pocos estudios para determinar la asociación entre los factores nutricionales y los DDE; de ellos se destacan los realizados en Bolivia por un grupo investigador de la Universidad de Washington con la colaboración del Centro Boliviano de Investigación y Desarrollo Socio-Integral 38,46 . http://erevistas.saber.ula.ve/ideula DEFICIENCIAS NUTRICIONALES COMO FACTOR ETIOLÓGICO…CORREDOR et al 58 Masterson et al desarrollaron un estudio de cohorte en 349 adolescentes (entre 10 y 17 años de edad) indígenas de la Amazonia Boliviana, para investigar la asociación de los siguientes factores: anemia, retardo de crecimiento, bajo peso e infección parasitaria ocurridos entre el primer y el cuarto año de edad y el desarrollo de defectos dentales (tanto en frecuencia como en extensión) de los incisivos permanentes superiores.…”
Section: Evidencia En Latinoaméricaunclassified
See 1 more Smart Citation